Culinary Globalization in Delhi: Filipino Sushi Chefs as Cultural Intermediaries - Lorenzana, Jozon A (Archīum Ateneo, 2023)
Culinary globalization in Indian cities has resulted in new patterns of food consumption and production. Aside from the increasing presence of global franchises such as Costa Coffee, McDonald’s and Kentucky Fried Chicken, local and foreign entrepreneurs have established restaurants that offer various national cuisines. In Delhi, for example, Japanese-themed restaurants cater to the city’s growing appetite for new culinary experiences. So far our knowledge of culinary globalization in Indian cities has focused on consumption: How emerging gastronomic patterns relate to identity formations. The production of cuisines as part of the city’s culinary globalization is rarely explored. In this paper; I focus on the role of Filipino ‘sushi chefs’ as cultural intermediaries who localize Japanese cuisine. This paper discusses their emergent practices of cultural mediation; namely adapting to local taste, peer mentoring and communicative labor. I argue that such practices of cultural mediation point to the social dynamics of cultural production.